Dynamics and immunological signature of γδ T cells following antiretroviral therapy initiation in acute HIV-1 Infection - Wang, Haihan; Li, Sibo; Wang, Rui; Wang, Xia; Zhang, Yang; Lu, Xiaofan; Sun, Jianping; Zhang, Tong; Huang, Xiaojie; Su, Bin; Wu, Hao; Li, Zhen (Frontiers in Immunology, 2025)
Early antiretroviral therapy (ART) is essential for controlling HIV-1 replication and boosting immune function. γδ T cells, as a vital component of the innate immune system, are implicated in the antiviral response. However, their immunological profile during acute HIV-1 infection and the early stages of ART remains unclear. This study aimed to delineate the immunological landscape of γδ T cells in individuals with acute HIV-1 infection undergoing early ART. We enrolled 65 participants who initiated ART immediately post-diagnosis and assessed the phenotypes and functions of γδ T cells using flow cytometry. We demonstrated that early ART significantly increased the frequency of Vδ2 T cells, while the Vδ1 T cell frequency remained stable and showed an inverse relationship with CD4+ T cell counts after ART. Early ART normalized the activation and PD-1 expression in Vδ1 and Vδ2 T cells, aligning with healthy controls (HCs) levels. Nevertheless, the proliferation of these cells, particularly within the PD-1+ subset, remains elevated post-ART. We also noted a reduction in perforin secretion in PD-1+ Vδ1 and Vδ2 T cells of people living with HIV (PLWH). Furthermore, Vδ1 T cells were identified as the predominant regulatory T cells, with TGF-β production and co-expression of CD127 and CXCR4, negatively correlated with CD8+ T cell activation. Our study elucidates the dynamic immunological characteristics of γδ T cells in acute HIV-1 infection and early ART, contributing to the understanding of their role in HIV-1 pathogenesis and the potential for γδ T cell-based immunotherapeutic strategies.